Monument Toppling: A Review of International Laws related to Cultural–Heritage Property and their Implications to Tourism (Nepalese Journal of Hospitality and Tourism Management, 2021)
Recent public conversations around cultural property law have exposed this area of international law to several gaps that exist in this field. Cultural property is key to tourism across the world and brings in the much-needed inflow of money in an economy due to its attraction. However, the entire premise of cultural property law is based on preservation and this common thread runs through almost all international legal instruments and most domestic legislations. In this paper, it is analysed through a careful perusal of the history of international cultural property law, if there is scope to introduce a limited right to destroy cultural – heritage property. This is explored through reading of international human rights law along with cultural property law to advance suggestions of rethinking and revamping this legal regime, as it has strong implications to tourism management. In the conclusion, the paper also explores how tourism management would also be reshaped if the international right to destroy oppressive imagery becomes a part of the discourse